International courts and domestic politics - Wind, Marlene, 1963- (Cambridge, United Kingdom ; New York, NY, USA : Cambridge University Press, 2018)
"Most studies describing this evolution have either drawn on classical legalistic approaches (see e.g. Aust and Nolte 2016; Keller and Stone Sweet 2008 or Mackenzie, Romano and Shany 2010) or been developed by constitutionalists?often from political science and sociology?preoccupied with mapping the global development and influence of ICs (see e.g. Slaughter 2000; Slaughter 2004; Slaughter and Burke-White 2006; Romano, Alter and Shany 2013 and Alter 2014). While the more classical legal scholarship has been predominated by accounts that outline principles and application of IC case law in national courts, constitutionalists have focused on actual practice, describing the evolution and functioning of ICs more broadly. What has unified both strands of research, however, is the often implicit description of a universal and unidirectional strengthening of legalization and judicialization in global affairs. The present volume puts the question in a different way. We do not from the outset normatively assume that ICs are important and powerful actors or that national actors without further ado cite, embrace or enter into a constructive dialogue with these supranational bodies. Rather what this book does is to ask?from a multidisciplinary perspective?how and to what degree do ICs actually influence, impose constraints on and create loyalty from those actors involved? It is our claim that rather little research has been occupied with the actual effects on the ground for those national courts, political institutions and citizens who are formally governed by the increased judicialization"--
Introduction / Marlene Wind -- Missing in action? : the rare voice of international courts in domestic politics / Lisa Conant -- What can financial markets tell us about international courts and deterrence? / Krzysztof Pelc and Jeffrey Kucik -- The Strasbourg court and domestic judicial politics / David Kosar -- It's a good idea ... isn't it? the impact of complementarity at the International Criminal Court on domestic law, politics and perceptions of sovereignty / Steven Freeland -- Rights-protecting iCourts : the curious case of the OP=ICESCR / Benjamin Perryman -- Re-assembling the French state via human rights : between human rights internationalism and political sovereignism / Mikael Rask Madsen -- Impact through trust : the CJEU as a trust-enhancing institution / Juan A. Mayoral -- Ideology and international human rights commitments in post-communist regimes : the cases of the Czech republic and Slovakia / Katarina Sipulova, Jozef Janovsky and Hubert Smekal -- Escalation and interaction : international courts and domestic politics in the law of state immunity / Philippa Webb -- National parliaments : obstacles or aid to the impact of international human rights bodies? / Jasper Krommendijk -- The European Court of Human Rights and Swiss politics : how does the Swiss judge fit in? / Odile Ammann -- The use of international jurisprudence by Israel's supreme court / Yael Ronen -- Laggards or pioneers? : when Scandinavian avant-garde judges don't cite international case law : a methodological framework / Marlene Wind.
Includes bibliographical references and index.
Online resource; title from PDF title page (EBSCO, viewed June 28, 2018).
eBooks on EBSCOhost
Keywords: International courts; International and municipal law; International law and human rights; Tribunaux internationaux; Droit international et droit interne; Droit international et droits de l'homme.; LAW -- International; International and municipal law; International courts; International law and human rights; International courts; National courts; International law and national law; Judicial dialogue; Politics; Electronic book